Exploration into the Practice of Curriculum Teaching Reform for Landscape Architecture in Higher Vocational Education under the “Design-Build” Workshop Model - Ye, Xue; Zhu, Siyuan; Peng, Jingen (Journal of Research in Vocational Education, 2025)
Through collecting, analyzing and researching the design-build course system and workshop process of domestic and foreign landscape architecture majors, we put forward a design-build workshop operation mode suitable for higher vocational landscape architecture majors, and establish a design-build progressive course system of modular and comprehensive courses. For the comprehensive course “Design Elite Skills Training”, we carried out the curriculum teaching reform, relying on the actual garden project - the future garden of 2022 Shenzhen Bougainvillea Show to carry out the practical teaching of “design-build” workshop, and complete the whole process of the experiment. This will provide a feasible direction for the reform of senior or vocational undergraduate landscape architecture.